Peningkatan Pemahaman Konsep Peserta Didik Melalui Penerapan Model Pembelajaran Problem Based Learning dengan Pendekatan Culturally Responsive Teaching pada Materi Persamaan Garis Lurus di Kelas VIII B SMP Negeri 3 Madiun Tahun Ajaran 2023/2024 - Iin Susilowati; Ika Krisdiana; Setyaningrum Nurul Hidayati (Journal on Education, 2024)
The ability to understand mathematical concepts is crucial for students to grasp the material flexibly and accurately. However, many students still struggle to comprehend these concepts when solving math problems, resulting in mere grades rather than true understanding. This study aims to enhance students' conceptual understanding through the implementation of Problem Based Learning (PBL) combined with Culturally responsive teaching (CRT) on the topic of linear equations in Class VIII B at SMP Negeri 3 Madiun during the 2023/2024 academic year. The method used in this research is Classroom Action Research (CAR) with 32 students as subjects. The results of this study show that the rubric scores for indicators of mathematical concept understanding were 42.19% in the pre-cycle, 61.72% in cycle I, and 83.59% in cycle II, which fall into the high category. Additionally, the percentage of student mastery increased from 71.88% with an average score of 78.72 in the pre-cycle to 90.63% with an average score of 82.63 in cycle I, and reached 100% with an average score of 87.56 in cycle II.